2021
DOI: 10.1590/1518-8345.3320.3386
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factorial analysis of the Maslach Burnout Inventory – Human Services Survey in health professionals in emergency services

Abstract: Objective: to confirm the factorial validity of the Maslach Burnout Inventory – Human Services Survey version in a sample of health professionals from the emergency services. Method: a quantitative, exploratory, descriptive and analytical study. Two hundred and eighty-two health professionals participated in the study. For data collection, a sociodemographic questionnaire and the Maslach Burnout Inventory were used. The psychometric sensitivity for the MBI-HSS items was estimated by measures of central tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
2
10
0
8
Order By: Relevance
“…Our figures were very similar to the internal consistency coefficients reported by Maslach et al [4] (0.90 for EE, 0.79 for DP, and 0.71 for PA). Similar results were also found in other studies [16,[33][34][35][36], even in those carried-out in other countries [14,15,17,[37][38][39][40][41][42], indicating that the scale maintains its validity despite crosscultural differences [12,15]. Although EFA showed a bit complex factorial structure splitting the MBI subscales in different factors, we think that our findings also confirm the three-dimensional factorial structure underlying the MBI-HSS as proposed by the original Maslach's model [4], as well as in other studies in which the factorial structure found as in the original version was maintained [15-17, 33, 36, 40, 42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our figures were very similar to the internal consistency coefficients reported by Maslach et al [4] (0.90 for EE, 0.79 for DP, and 0.71 for PA). Similar results were also found in other studies [16,[33][34][35][36], even in those carried-out in other countries [14,15,17,[37][38][39][40][41][42], indicating that the scale maintains its validity despite crosscultural differences [12,15]. Although EFA showed a bit complex factorial structure splitting the MBI subscales in different factors, we think that our findings also confirm the three-dimensional factorial structure underlying the MBI-HSS as proposed by the original Maslach's model [4], as well as in other studies in which the factorial structure found as in the original version was maintained [15-17, 33, 36, 40, 42].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have been published carrying out exploratory and/or confirmatory analyses of the factorial structure of the MBI in different professional groups [12]. Although the studies carried out with health professionals have focused mainly on nursing professionals, both emergency and non-emergency nursing care [13,14], even exploring differences between countries [15], there are also some studies including physicians [16], and including all emergency professional profiles [17]. But we are not aware of any study exploring the factorial validity of the MBI-HSS in a cohort of urgency healthcare professionals in Spain.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout was measured using the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) (Pereira et al 2021;Maslach and Jackson 1981). The instrument has 22 selfcompletion items, divided by three dimensions: emotional exhaustion, measured with nine items; depersonalization, measured by five items; and personal fulfillment, measured by eight items.…”
Section: Methodsmentioning
confidence: 99%
“…After answering, each participant returned the sealed envelope, without their names, preserving their anonymity. Each participant received an envelope with a questionnaire composed of demographic variables, occupational variables, information on the impact of the COVID-19 pandemic on their day-to-day life (insomnia, lack of appetite, irritability, decreased libido, fear of being infected, fear of infecting loved ones, overspending) and the Maslach Burnout Inventory (MBI) questionnaire,17 18 translated and transculturally validated for Portuguese in Brazil, which has acceptable psychometric properties when compared with its original version in English 6 19. The full questionnaire (translated to English) can be found in the online supplemental material.…”
Section: Introductionmentioning
confidence: 99%